IS HEMOGLOBIN E GENE WIDELY SPREAD IN THE STATE OF MADHYA PRADESH IN CENTRAL INDIA? EVIDENCE FROM FIVE TYPICAL FAMILIES - R S Balgir (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Red cell inherited hemoglobin anomalies are commonly encountered in the central region of India. These cause a public health concern due to high degree of morbidity, mortality, and fetal loss in the backward, underprivileged, and vulnerable people. Purpose: To report five typical families of hemoglobin E disorders identified for the first time in the state of Madhya Pradesh from central India. Methods: Out of a total of 445 couples/families (excluding the present study) with 1526 persons (848 males and 678 females) referred from a tertiary hospital in central India for investigations of anemia/hemoglobinopathies during the period from March 2010 to February 2014, we came across five typical rare couples/families of hemoglobin E disorders worthy of detailed investigations. Laboratory investigations were carried out following the standard procedures after cross checking for quality control from time to time. Results: For the first time, we have encountered nine cases of heterozygous hemoglobin E trait, two members with hemoglobin E-β-thalassemia (double heterozygosity), two cases of sickle cell-hemoglobin E disease (double heterozygosity), and none with homozygous hemoglobin E. Cases  of hemoglobin E trait, hemoglobin E-β-thalassemia, sickle cell-β-thalassemia and sickle cell-E disease showed moderate to severe anemia, and target cells, and reduced values of red cell indices like RBC, Hb level, HCT, MCV, MCH and MCHC, representing abnormal hematological profile and clinical manifestations before blood transfusion. Conclusions: Double heterozygosity for hemoglobinopathies such as occurrence of β-thalassemia mutation with structurally abnormal hemoglobins (Hb S and Hb E) is a rare entity, but occurs with severe clinical manifestations only in those areas or communities where these are highly prevalent, testifying the migrations and genetic admixture. Distribution of hemoglobin E and β-thalassemia in different districts of Madhya Pradesh indicates that abnormal Hb E gene has wide spread and needs prevention for the rehabilitation of vulnerable people in central India.